PERAN MASYARAKAT DALAM UPAYA KONTRA RADIKALISASI DI DUNIA MAYA - Muhammad Farhan Makarim (2022)
The rapid development of the times makes everything easier, especially in the dissemination of information in cyberspace. In this era, online media has become the life of every individual. It is undeniable that almost all activities require the internet. However, this is actually used by radicals to spread their ideology in cyberspace. This is what motivated the author to conduct research to discuss how the process of counter-radicalization and deradicalization can involve community components so as to create a community role that can prevent radicalism in cyberspace. The purpose of this study was to determine early prevention efforts that can be implemented in counter-radicalization efforts in cyberspace. The method used in this research is normative juridical which is carried out through a statutory approach and a conceptual approach. While the data used are primary and secondary data. The results of this study indicate that community empowerment through the institution closest to the community, namely Karang Taruna is one of the roles of the community that provides direct appeals about the content of radicalism in cyberspace by educating members of the Youth Organization so that they can provide counter narratives and socialize the community in their scope,